A new species of Rhynchohydracarus Lundblad 1936 (Acariformes: Hydrachnidiae: Hydryphantoidea: Rhynchohydracaridae) from central Brazil, with DNA barcodes, a key for known species and a proposal for the homologies of dorsalia, ventralia, lateralia and glandularia for the family - Castro, Luiz A. S. de [UNESP] (2022)
We describe a new species of the genus Rhynchohydracarus, R. armiger n. sp., from central Brazil, including complete information for female , male, accompanied by DNA barcode sequences. It is the first record of water mites for the running waters of the Cerrado biome. We present a proposal for the homologies of dorsalia, ventralia , glandularia in Rhynchohydracaridae and also provide an identification key for the known species of the genus.